2004
DOI: 10.1186/1476-069x-3-1
|View full text |Cite
|
Sign up to set email alerts
|

Maternal concentration of polychlorinated biphenyls and dichlorodiphenyl dichlorethylene and birth weight in Michigan fish eaters: a cohort study

Abstract: Background: Studies on maternal exposure to polychlorinated biphenyls (PCBs) reported inconsistent findings regarding birth weight: some studies showed no effect, some reported decreased birth weight, and one study found an increase in weights. These studies used different markers of exposure, such as measurement of PCBs in maternal serum or questionnaire data on fish consumption. Additionally maternal exposures, such as dichlorodiphenyl-dichloroethylene (DDE), which are related to PCB exposure and may interfe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
72
1
1

Year Published

2005
2005
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(82 citation statements)
references
References 54 publications
8
72
1
1
Order By: Relevance
“…Maternal serum and umbilical cord blood levels of p,p´-DDT and/or p,p´-dichlorodiphenyldichloroethylene (p,p´-DDE), a metabolite of p,p´-DDT, have been associated in some studies with preterm birth (Longnecker et al 2001;Ribas-Fito et al 2002;Saxena et al 1980;Wasserman et al 1982), decreased birth weight (O'Leary et al 1970;Weisskopf et al 2005), or intrauterine growth retardation (Longnecker et al 2001;Siddiqui et al 2003). In other studies, increased levels of p,p´-DDT and/or p,p´-DDE in maternal serum, cord blood, or breast milk were not related to either decreased infant birth weight (Bjerregaard and Hansen 2000;Dewailly et al 1993b;Gladen et al 2003;Karmaus and Zhu 2004;Needham et al 2005;Rogan et al 1986) or preterm birth (Berkowitz et al 1996;Needham et al 2005;Torres-Arreola et al 2003).…”
mentioning
confidence: 76%
“…Maternal serum and umbilical cord blood levels of p,p´-DDT and/or p,p´-dichlorodiphenyldichloroethylene (p,p´-DDE), a metabolite of p,p´-DDT, have been associated in some studies with preterm birth (Longnecker et al 2001;Ribas-Fito et al 2002;Saxena et al 1980;Wasserman et al 1982), decreased birth weight (O'Leary et al 1970;Weisskopf et al 2005), or intrauterine growth retardation (Longnecker et al 2001;Siddiqui et al 2003). In other studies, increased levels of p,p´-DDT and/or p,p´-DDE in maternal serum, cord blood, or breast milk were not related to either decreased infant birth weight (Bjerregaard and Hansen 2000;Dewailly et al 1993b;Gladen et al 2003;Karmaus and Zhu 2004;Needham et al 2005;Rogan et al 1986) or preterm birth (Berkowitz et al 1996;Needham et al 2005;Torres-Arreola et al 2003).…”
mentioning
confidence: 76%
“…Several studies of lower-level PCBs exposure during pregnancy observed associations with decreased birth weight and other growth parameters (Fein et al, 1984;Rylander et al, 1996: Rylander et al, 1998Patandin et al, 1998;Karmaus and Zhu, 2004;Hertz-Picciotto et al, 2005;Sagiv et al, 2007;Sonneborn et al, 2008). In the Lake Michigan fish consumer study, cord serum PCBs levels predicted LBW and smaller birth head circumference (Fein et al, 1984).…”
Section: Introductionmentioning
confidence: 99%
“…A meta-analysis comparing prenatal PCB exposure and birth weight effects across 12 European birth cohorts found a significant negative correlation between cord blood PCB levels and birth weight [11]. Multiple studies have confirmed that low-level PCB exposure during the perinatal period can significantly affect fetal growth and birth weight [12,[14][15][16][17][18][19], although other studies found that PCBs have minimal or no effect [20,21]. Nonetheless, the decreased body weight can persist to preschool ages and is concomitant with hypotonia and diminished physical activity [22,23].…”
Section: Introductionmentioning
confidence: 99%
“…The developmental origins of health and disease hypothesis, derived from the thrifty phenotype hypothesis put forth by Barker and Hales in 1992 [5], postulates that low birth weight offspring can result from insufficient nutrition in the intrauterine environment, leading to metabolic and other health derangements later in life [5][6][7][8][9][10]. In fact, maternal serum PCB levels in humans negatively correlate with infant birth weight and gestational age [11][12][13][14][15][16][17]. A meta-analysis comparing prenatal PCB exposure and birth weight effects across 12 European birth cohorts found a significant negative correlation between cord blood PCB levels and birth weight [11].…”
Section: Introductionmentioning
confidence: 99%